Psychological experiences of family caregivers of children with intellectual disability - Sadiki, Tshimangadzo Getrude (My University, 2016)
The aim of this study was to determine the psychological experiences of family caregivers of children with an intellectual disability. The study was conducted along the lines of an exploratory sequential mixed-method design. Firstly, 15 family caregivers were purposively sampled as participants. They described their experiences of caring for children with a formal diagnosis of mild intellectual disability. The research question, which was used as a “grand-tour” question, was: “What are the psychological experiences of family caregivers of children with an intellectual disability?” Themes that emerged included the following: understanding intellectual disability; disclosure of the disability as a result of schooling difficulties; reaction to the disclosure of the disability; challenging behaviour of the child’s integration into the family system, unemployment and financial strains due to the child’s condition and community reaction; social support and stigmatisation. In the quantitative aspect of the study, the researcher used a close-ended questionnaire to collect data from one hundred self-declared primary family caregivers (one per household) of children with an intellectual disability. Results of regression analysis indicated that psychological wellbeing as measured by the Psychological General Well Being Index and its dimensions was predicted mainly by psychological stress and family support. Significant other support and support from friends only predicted life satisfaction. Policy recommendations are advanced based on the findings of the study.
Thesis (M. A. (Psychology)) -- University of Limpopo, 2016
Keywords: Caregivers; Intellectual disability; Psychological experiences; Children with mental disabilities; Children with mental disabilities; Children with mental disabilities -- Care; Families of the mentally ill; Mental retardation; Caregivers -- Psychology